2007
DOI: 10.1007/s10585-007-9061-2
|View full text |Cite
|
Sign up to set email alerts
|

Solitary bone metastasis in the tibia as a presenting sign of endometrial adenocarcinoma: a case report and the review of the literature

Abstract: Patients with endometrial adenocarcinoma presenting an isolated skeletal metastasis may exhibit an unusual group with a better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
(28 reference statements)
0
32
1
Order By: Relevance
“…In an autopsy study, the corresponding frequency was 25–75% [6]. Bone metastasis are mostly seen as recurrence and survival is better when compared to those who sustained solitary bone metastasis at primary diagnosis [1], [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an autopsy study, the corresponding frequency was 25–75% [6]. Bone metastasis are mostly seen as recurrence and survival is better when compared to those who sustained solitary bone metastasis at primary diagnosis [1], [7].…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial adenocarcinoma presenting with a bone metastasis at the first diagnosis is rarely seen. Usually first sign is abnormal uterine bleeding and pelvic pain, yet endometrial adenocarcinoma diagnosed after tibial metastases have been reported in 7 cases up to now [1], [3], [9], [10], [11], [12], [13]. Metastatic bone disease is usually seen after first diagnosis of endometrial adenocarcinoma and duration between diagnosis and metastasis is 6 months to 5 years [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is marginal benefit on survival with chemotherapy and radiotherapy is effective in reducing local recurrence and controlling cancer-related pain as well as haemorrhage. Other option includes amputation, which should be considered in case of uncontrollable pain, haemorrhaged or serious infection 79. Reconstructive surgery is not recommended due to poor prognosis.…”
Section: Discussionmentioning
confidence: 99%